Monoclonal antibodies to human intermediate filament proteins. II. Distribution of filament proteins in normal human tissues. - Gown, A. M. (1984)
Monoclonal antibodies generated against different human intermediate filament (IF) proteins were assayed on fixed, embedded tissue by the biotin-avidin-immunoperoxidase method for evaluation of the tissue specificity of these antibodies. An antibody (43 beta E8) made to fibroblast IF protein stains mesenchymal tissue such as endothelium, histiocytes, stromal fibroblasts, and Schwann cells but does not stain epithelium, skeletal muscle, lymphocytes, or neurons. Three different anti-cytokeratin antibodies decorate epithelium in three unique patterns. One (35 beta H11) stains all nonsquamous epithelium but fails to recognize squamous epithelium. Antibody 34 beta E12 stains the full thickness of squamous epithelium and ductular epithelium but does not react with hepatocytes, pancreatic acinar cells, proximal renal tubules, or endometrial glands. Antibody 34 beta B4 stains only the suprabasal portion of squamous epithelium. None of these three anti-cytokeratin antibodies reacts with nerve or mesenchymal tissue. Two anti-neurofilament antibodies recognize only neurons, failing to react with epithelial or mesenchymal tissue. We conclude that these anti-intermediate filament antibodies can be used as tissue-specific markers. Neoplasms retain the same intermediate filament patterns as the normal parental tissue; therefore, these antibodies can be used as diagnostic aids in surgical pathology.